(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
The development of information technology has revolutionized the way consumers shop. Electronic commerce (e-commerce) has become an important channel for consumers to purchase products and services. In the context of e-commerce, consumer knowledge sharing behavior, where consumers share information and experiences about products and services with others, plays an important role in influencing consumer purchasing decisions. The research design in this study is descriptive quantitative using purposive sampling technique. The research method uses surveys and data analysis to explore consumer knowledge sharing behavior on consumer purchasing behavior in Indonesia. Data was collected through an online survey of the online shopping consumer population in Indonesia with a sample size of 102 respondents. The research data was analyzed using SEM-PLS. The findings of this study are expected to provide insights for practitioners and academics in understanding the dynamics of electronic commerce, as well as provide a foundation for the development of more effective and sustainable marketing strategies in the future.